Current reversal in a symmetric periodic potential. (May 2017) - Chen, Ruyin; Zhang, Guangwen; Wang, Chaojie; Nie, Linru; Chen, Chongyang
Abstract: In previous research work, investigators have focused mainly on noise-induced current reversal (CR) in spatially ratchet systems, while less effort has been devoted to the CR in a spatially symmetric periodic potential. Transport of an underdamped Brownian particle in a symmetric periodic potential driven by correlated noises (correlation between additive noise and multiplicative noise) and periodic signals is investigated. By means of numerical calculations, we obtain average velocity (current) of the system. The results indicate that motion direction of the particle changes with increment of the additive or multiplicative noise intensity in case of the correlated noises, i.e., CR. Our further investigations show that the additive signal and the correlation between the noises are two necessary ingredients for the CR in the spatially symmetric system. And the CR is brought about by the symmetry breaking induced by the noises, not by temporal symmetry breaking.